2022
DOI: 10.1021/acsanm.2c02602
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanosphere-Encapsulated Fe Core–Shell Structures for Catalytic CO2 Hydrogenation

Abstract: We synthesized a unique carbon nanosphere (CNS)encapsulated Fe core−shell catalyst (CNS−Fe) for CO 2 hydrogenation. The synthesized CNS−Fe catalyst exhibited a core−shell structure with a core of ca. 40 nm containing iron species and a shell thickness of ca. 10 nm composed of mainly graphitic carbon. X-ray diffraction, X-ray photoelectron spectroscopy, Raman spectroscopy, and thermogravimetric analysis were used to characterize the fresh and spent CNS−Fe catalysts and reveal a mixture of Fe 3 O 4 , metallic Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 68 publications
(124 reference statements)
3
20
0
Order By: Relevance
“…We further noted that the intensity of the (110) Fe and (510) Fe 5 C 2 peaks was amplified with rising temperatures, indicative of particle growth (Figure A). Concurrently, the increasingly distinct peak at 24.3° confirms the progressive graphitization of carbon beyond 850 °C, specifically representing the (002) plane of graphitized carbon …”
Section: Results and Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…We further noted that the intensity of the (110) Fe and (510) Fe 5 C 2 peaks was amplified with rising temperatures, indicative of particle growth (Figure A). Concurrently, the increasingly distinct peak at 24.3° confirms the progressive graphitization of carbon beyond 850 °C, specifically representing the (002) plane of graphitized carbon …”
Section: Results and Discussionmentioning
confidence: 80%
“…All of these catalyst variants were subjected to a reduction and activation process at 350 °C for 2 h in a 50% H 2 stream. This specific set of activation conditions was meticulously chosen based on insights garnered from our previous hydrogen temperature-programmed reduction (H 2 -TPR) studies . By implementing these conditions, we strategically facilitated the partial reduction of surface functional groups present on the carbon material, a step that plays a pivotal role in amplifying the catalytic activity of the system.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Due to special electronic properties and space limitations, the metal inside the core-shell structure has more catalytic activity than the metal deposited on the surface. For example, the core-shell structure prepared by Weber et al has a graphite-like shell with abundant defect sites, which showed high catalytic performance in HER (Weber et al, 2022).…”
Section: Electrocatalytic Water Splittingmentioning
confidence: 99%
“…[15] The CCH route comprises reverse water gas reaction (RWGS) and Fischer-Tropsch synthesis. [20][21][22] These two reactions use Fe 3 O 4 and FeC x as active catalytic sites, respectively. Although they are two different active sites, both are compounds of Fe, and they can be generated in situ simultaneously after activation.…”
Section: Introductionmentioning
confidence: 99%
“…This route is friendly for product selectivity, but its CO 2 conversion is generally low [15] . The CCH route comprises reverse water gas reaction (RWGS) and Fischer‐Tropsch synthesis [20–22] . These two reactions use Fe 3 O 4 and FeC x as active catalytic sites, respectively.…”
Section: Introductionmentioning
confidence: 99%